PREVALENCE OF SCIENCE ANXIETY IN SECONDARY SCHOOL: AN EMPIRICAL STUDY OF THE ENUGU STATE POST-PRIMARY EDUCATION SYSTEM - Adukwu, Bibian (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The development of science education is among the core objective of the contemporary education ecosystem. Numerous disparate studies have underscored the pattern and prospects of science anxiety in the school system in Nigeria. However, little is known about the phenomenon's existence in the post-primary education system of Enugu state, Nigeria. The present study examined the prevalence of science anxiety at the junior secondary school level in Enugu state. One hundred and eighty-five students drawn from public and private secondary schools in the Enugu State participated in the study. Their level of science anxiety was assessed with the Science Anxiety Scale (Oludipe & Oludipe, 2019). The result indicated a high level of science anxiety (54.3%) among the respondents. Also, it was found that females showed more science-related anxiousness than their male counterparts. The result has implications for the development of science education in Nigeria.